Tensile strength and thermal cycle analysis of AA6061 friction weld joints with different diameters and various friction times - Irawan, Yudy Surya; Choiron, Moch Agus; Suprapto, Wahyono (Eastern-European Journal of Enterprise Technologies, 2021)
The paper reports measurement of tensile strength and the thermal cycle of AA6061 aluminum alloy circular bar friction weld with different diameters and various friction times. A continuous drive friction welding (CDFW) of AA6061 was conducted to weld the AA6061 circular bar with different diameters of 30 mm for the rotating part and 15 mm for the stationary part. The CDFW process was carried out with the revolution speed of 1,600 rpm, the initial compressive force of 2.8 kN during the friction stage for various friction times of 10, 12, and 14 seconds, and an upset force of 28 kN for 60 seconds. The flash temperature was measured using a digital infrared thermometer gun. Computer simulation using the finite element method was also done by coupling transient thermal and static structural methods. The flash temperature becomes higher along with increasing friction time based on the digital infrared thermometer gun measurement and finite element analysis. The results of tensile strength testing show that the specimen with a friction time of 12 seconds has the highest tensile strength. Based on the hardness testing result, it is found that the specimen with a friction time of 10 seconds has higher hardness, but it has an incomplete joint flash so that the tensile strength is lower than that of the specimen with a friction time of 12 seconds. Besides, the hardness of the specimen with a friction time of 12 seconds is higher than that of the specimen with a friction time of 14 seconds. The flash size becomes bigger along with the increase of the friction time based on the macrostructure observation on the longitudinal section of the CDFW specimen. It is confirmed by the temperature measurement and finite element analysis that the specimen with a friction time of 12 seconds has heat input to form the CDFW joint that has a maximum tensile strength in the range of this study